Introducing a Novel Personalized Microbiome-Based Treatment for Inflammatory Bowel Disease: Results from NostraBiome’s Internal Validation Study - Adrian Goldiș; Radu Dragomir; Marina Adriana Mercioni; Christian Goldiș; Diana Sirca; Ileana Enatescu; Oana Belei (Biomedicines)
Background/Objectives: Inflammatory bowel disease (IBD), encompassing ulcerative colitis and Crohn’s disease, is characterized by chronic gut inflammation driven by microbial dysbiosis and immune dysfunction. Current therapies primarily involve anti-inflammatory and immunomodulatory strategies; however, many patients experience an inadequate response or a gradual loss of efficacy over time. This study evaluates the clinical efficacy of personalized microbiome modulation (PMM)—an AI-driven intervention designed to restore microbial balance and improve key treatment outcomes such as symptom control and remission rates. Methods: This was a single-arm, open-label validation trial involving 27 patients with moderate-to-severe IBD who had experienced prior treatment failure. Participants underwent three months of PMM, which included personalized dietary modifications, targeted probiotic supplementation, and antimicrobial interventions based on gut microbiome sequencing. Primary outcomes included stool frequency and consistency as well as inflammatory markers (C-reactive protein and fecal calprotectin), while secondary outcomes assessed nutritional status, metabolic function, and quality of life. Statistical analyses included paired t-tests and repeated measures ANOVA to determine significant changes over time. Results: PMM led to significant clinical improvements, including a 58% reduction in stool frequency (p < 0.001) and improved stool consistency. CRP and fecal calprotectin levels decreased markedly (p < 0.001), suggesting reduced systemic inflammation. Additionally, iron, vitamin B12, and vitamin D deficiencies improved (p < 0.001), alongside weight gain and increased energy levels. Notably, patients on anti-TNF biologics showed enhanced response rates, suggesting potential synergistic effects between microbiome modulation and biologic therapy. Conclusions: This study highlights PMM as a promising adjunctive therapy for IBD, demonstrating benefits across clinical, inflammatory, and metabolic parameters. While findings support the role of microbiome-targeted interventions in disease management, larger randomized controlled trials are required to confirm the long-term efficacy and applicability in broader patient populations.